How to Improve through Media Strip Story? - Isma Maryamah; Yayan Nurbayan; Mia Nurmala; Anpas Tohir Maulana (Universitas Pendidikan Indonesia (UPI), 2023)
Reading ability is a person's ability to understand written content and then manifest it by reciting it orally. The ability to read is the basis for developing one's language skills because Arabic is always related to Arabic texts. The problem found by researchers at Madrasah Diniyah Almunawarotul Banat is the need for students' ability to read and understand the contents of Arabic texts. This study aims to improve the reading skill (maharah qiraah) of fifth-grade students at Madrasah Diniyah Almunawarotul Banat in learning Arabic using the Strip Story method. This research is a classroom action research (CAR) that focuses on action research, which consists of two cycles, with the subject being fifth-grade students at Madrasah Diniyah Almunawarotul Banat, a total of 20 people. The results of this study indicate that the method of story strips can improve students' ability to read Arabic texts. In the first cycle, only a small number of students could read Arabic sentences, with an average of 66.5%. In the second cycle, almost 80% of students could read Arabic texts; judging from the average obtained, it was 75.45%.